Local pharmaceutical research and development capacity in a developing country: a qualitative exploration of perspectives from key stakeholders in Ethiopia - Muluken Nigatu Selam; Samuel Abera; Helen Geremew; Eskinder Eshetu Ali (Taylor & Francis Group, 2022)
Purpose Despite its importance in ensuring sustainable healthcare, there are huge challenges with pharmaceutical research and development (R&D) especially for developing countries mainly due to the high investment costs naturally associated with such activities. In this regard, the pharmaceutical sector in Ethiopia, the most populous nation in East Africa, faces numerous challenges. The current study aimed at assessing the R&D capacity of the local pharmaceutical manufacturers from the perspectives of key informants working in the companies and supporting government offices and education institutions. Methods A qualitative study design employing in-depth interviews using semi-structured interview guides with flexible probing techniques was used for data collection. The study involved purposively selected participants who represented major stakeholders such as managers in the R&D departments of pharmaceutical manufacturers, officers and leaders in concerned government agencies and researchers in a local university. All transcribed interviews were subjected to thematic analysis and the Qualitative Data Analysis software in family R (RQDA) was used for data analysis. Results A total of 14 participants were involved in the study and three major themes were identified from the interviews. Current R&D capacity, opportunities and challenges for involvement in R&D were the major themes. Under current R&D capacity, the weak R&D status of local pharmaceutical plants and minimal university-industry linkage were identified. The challenges of pharmaceutical R&D in Ethiopia included weak governmental and managerial support; difficult procurement processes for R&D input; and the high cost of R&D. Availability of trainable human power and planned government incentives were identified as the opportunities. Conclusion Overall, there is a low level of R&D capacity in local pharmaceutical industries and timely interventional strategies should be implemented through collaboration of academia, research institutions and pharmaceutical industries.